High‐Performance Production of Biosurfactant Rhamnolipid with Nitrogen Feeding. Issue 2 (22nd January 2019) - Wu, Tingyu; Jiang, Jingjing; He, Ni; Jin, Mingjie; Ma, Kefeng; Long, Xuwei
Abstract: Nitrate is one of the most important factors for fermentative production of rhamnolipid, while it has not yet been conclusively demonstrated that nitrogen limitation or abundance is beneficial for improvement of rhamnolipid production. This study clarified that high concentration of NaNO3 is conducive for high‐performance production of rhamnolipid. An optimum rhamnolipid yield was achieved by 43.3 g L −1 with an initial concentration of NaNO3 equal to 10 g L −1 during the regular fed‐batch fermentation process by Pseudomonas aeruginosa ATCC 9027. Additionally, this rhamnolipid production was further improved to 61.2 g L −1, which was two folds higher than that value obtained during batch fermentation, when the NaNO3 concentration was maintained about 5 g L −1 . Furthermore, specific volume productivity of rhamnolipid was improved by over 30% in the presence of NaNO3 at concentration ranging from 5 to 6 g L −1 during sequential fed‐batch fermentation, resulting a high value of 0.4 and 0.59 g L −1 h −1 within one batch of sequential fed‐batch fermentation for a period of 17 days by P. aeruginosa ATCC 9027 and PAO1, respectively. It seems that sustaining high‐concentration NaNO3 during fed‐batch fermentation is advantageous for high‐performance production of rhamnolipid.